Physical and Chemical Characteristic of Young Coconut Leaves (Cocos nucifera L.) as Traditional Packaging - Uswatun Hasanah; Edlina Putri Sukma Dewi; Umar Santoso; Supriyadi Supriyadi (Indonesian Food and Nutrition Progress, 2020)
Traditional food is usually packed with natural packaging materials such as young coconut leaves (janur), but a little scientific information is available related to the packaging material. This study aimed to examine the physical and chemical characteristics of fresh and steamed janur (30 minutes steaming at 100 °C). The physical and chemical properties of janur were expected to be the basis for the development of janur as an environmentally friendly packaging material. The results showed that fresh and steamed janur color was greenish-yellow and brownish-yellow. The fresh and steamed janur had a tensile strength 19.19 MPa and 30.62 MPa; water content 73.54% and 69.57%; and fat content 1.85% and 0.54%, respectively. After steaming, the microstructure of the cells became finer and irregular. The dominant fatty acid in fresh janur and steamed janur was palmitic acid (24.27%), and palmitoleic acid (38.56%), respectively. The treatment of steaming of janur influenced the physical and chemical characteristics of packaging materials.